Industrial pollution related health problems among residents of a rural area in central Kerala - Thadathil, Suchithra Erath; Viswambharan, Jaya Koothupalakkal; Premdas, Alok Kanjhoor; Raj, Ashwin (International Journal Of Community Medicine And Public Health, 2021)
Background: Air pollution leads to several health effects, the major systems affected were respiratory, dermatology, neurology and ophthalmology. This study is an attempt to find out various health effects of pollution, from a food factory to the nearby residents. Methods: A cross sectional comparative study was performed on 248 residents nearby a food factory, situated in rural area of Thrissur district and a comparative group of 266 participants taken 5km away from this factory. Results: Both the groups were comparable in socio-demographic profile except religion and occupation. There was no statistically significant difference (p>0.05) between the use of firewood in both the groups. The symptoms of major systems involved were respiratory (odds ratio 3.9, 95% CI 2.2 to 6.8), dermatological (odds ratio 18.3, 95% CI 8.3 to 40.7), neurological (odds ratio 13.5, 95% CI 4.1 to 44.7) and ophthalmological (odds ratio 5.9, 95% CI 2.6 to 13.6). The major symptoms complained by them were pruritus (32.7%), skin lesions (17.7%), breathlessness (16.9%), itching eye (13.3%) watering from eye (11.7%) and headache (11.3%). All these symptoms among the case group compared to control group were very high and these associations were highly statistically significant (p<0.001). Conclusions: This study showed an increased occurrence of adverse health effects among the individuals who were residing near the food factory. Therefore this study points out the possibility of environmental pollution (mainly air pollution) as a main factor for the increased prevalence of symptoms among those who reside nearby the factory.